PENERAPAN GAMIFIKASI PADA PENILAIAN ABSENSI (PenA) UNTUK MENINGKATKAN MOTIVASI BIMBINGAN - Rahardja, Untung; Aini, Qurotul; Hayat, Abdul; Santoso, Nuke Puji Lestari (EDUTECH, 2019)
Entering the disruptive 4.0 era, information technology is increasingly needed in the education sector. In presenting information, it should be up to date and have a sophisticated information technology breakthrough. At Higher Education there is an online attendance system that is using PenA (Attendance Assessment). However, the process of guidance activities is not yet maximal in the presence of guidance students. There are 2 (two) problems in this study, namely the absence of a system that is able to motivate the presence of student guidance and the results of the guidance time. To solve these 2 (two) problems, the existence of gamification techniques on the Attendance Assessment (PenA) website system in order to increase student motivation in the tutoring activities of the supervisor so that students are more diligent in the presence of guidance. The gamification can be said to be a reward in the Attendance Assessment (PenA) system. From the application of the gamification technique on Attendance Assessment (PenA) 7 research methods were used and 7 (seven) review literature. Attendance Assessment (PenA) now has the advantage of logging in using SSO, and also being absent by scanning Qr Code. With the gamification technique on Attendance Assessment (PenA) it is able to provide a level of motivation for students in their attendance. As well as visible achievements of students in craft attendance in guidance.Memasuki era disruptif 4.0 kini teknologi informasi semakin dibutuhkan dalam bidang pendidikan. Dalam menyajikan informasi semestinya sudah up to date dan memiliki terobosan teknologi informasi yang canggih. Pada Perguruan Tinggi terdapat sebuah sistem kehadiran secara online yaitu dengan menggunakan PenA (Penilaian Absensi). Namun proses kegiatan bimbingan dirasa belum cukup maksimal dalam kehadiran mahasiswa bimbingan. Terdapat 2 (dua) permasalahan pada penelitian ini yaitu belum adanya sistem yang mampu memotivasi kehadiran mahasiswa bimbingan dan hasil capaian waktu bimbingan. Untuk menyelesaikan 2 (dua) permasalahan tersebut maka adanya teknik gamifikasi pada sistem website Penilaian Absensi (PenA) guna meningkatkan motivasi mahasiswa dalam kegiatan bimbingan belajar terhadap dosen pembimbing sehingga mahasiswa lebih rajin dalam kehadiran bimbingan. Gamifikasi tersebut dapat dikatakan sebagai reward pada sistem Penilaian Absensi (PenA). Dari penerapan teknik gamifikasi pada Penilaian Absensi (PenA) digunakan 7 langkah metode penelitian dan 7 (tujuh) literatur review. Penilaian Absensi (PenA) kini memiliki keunggulan yaitu login menggunakan SSO, dan juga absen dengan melakukan scanning berupa Qr Code. Dengan adanya teknik gamifikasi pada Penilaian Absensi (PenA) mampu memberikan tingkat motivasi mahasiswa dalam kehadiran yang dicapainya. Serta terlihat capaian mahasiswa dalam kerajinan kehadiran dalam bimbingan.